NK cells with decreased expression of multiple activating receptors is a dominant phenotype in pediatric patients with acute lymphoblastic leukemia - Valenzuela-Vázquez, Lucero; Nuñez-Enriquez, Juan Carlos; Sánchez-Herrera, Jacqueline; Medina-Sanson, Aurora; Pérez-Saldivar, María Luisa; Jiménez-Hernández, Elva; Martiín-Trejo, Jorge Alfonso; Del Campo-Martínez, María de Los Ángeles; Flores-Lujano, Janet; Amador-Sánchez, Raquel; Mora-Ríos, Félix Gustavo; Peñaloza-González, José Gabriel; et al. (Frontiers in Oncology, 2022)
NK cells have unique attributes to react towards cells undergoing malignant transformation or viral infection. This reactivity is regulated by activating or inhibitory germline encoded receptors. An impaired NK cell function may result from an aberrant expression of such receptors, a condition often seen in patients with hematological cancers. Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer worldwide and NK cells have emerged as crucial targets for developing immunotherapies. However, there are important gaps concerning the phenotype and behavior of NK cells during emergence of ALL. In this study we analyze the phenotype and function of NK cells from peripheral blood in pediatric patients with ALL at diagnosis. Our results showed that NK cells exhibited an altered phenotype highlighted by a significant reduction in the overall expression and percent representation of activating receptors compared to age-matched controls. No significant differences were found for the expression of inhibitory receptors. Moreover, NK cells with a concurrent reduced expression in various activating receptors, was the dominant phenotype among patients. An alteration in the relative frequencies of NK cells expressing NKG2A and CD57 within the mature NK cell pool was also observed. In addition, NK cells from patients displayed a significant reduction in the ability to sustain antibody-dependent cellular cytotoxicity (ADCC). Finally, an aberrant expression of activating receptors is associated with the phenomenon of leukemia during childhood.